Análisis de la gestión de las cuentas por cobrar de Medilink S. A., durante el periodo 2021. - Ramos Zambrano, Karen Estefanía (2022)
The asset that companies have is, of course, one of the fundamental pillars, it is required to be able to carry out the different obligations, be they rates, contributions, payments to the IESS, among others. All of these refunds are defined as part of the asset to be used after a certain period of time, to be made on an annual basis to establish the balance and determine if the company meets what is required to survive in the market. Medilink Company is a medical services company that provides medical check-ups, medications, professionally recommended treatments and as a private sector company it is essential that they charge for each service they provide, unlike companies in the public sector pharmaceutical industry, since they are state property and therefore should not charge, unless they are distinctions of specific services beyond the limits of the hospital, such as complex complications, hospitalization of patients, among others. This study is quantitative and qualitative because it uses numerical values that were found when requesting the company's accounts receivable for the 2021 period and it is qualitative since it is based on these data to determine if what is entered represents a profit or loss for the business and determine the efficiency and effectiveness of the human resource it possesses, based on what the accounts receivable item shows. This research deals with analyzing how the company manages customer accounts during the year 2022.